Bahasa Arab untuk Tujuan Khusus di Indonesia dan Malaysia: Tinjauan Normatif dan Empiris - Mauidlotun Nisa; Syamsul Arifin (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2020)
This article aims to uncover the paradigm of Arabic for special purposes in Indonesia and Malaysia through formal and informal institutions. This qualitative field study makes use of primary data obtained from curriculum documents and interviews with teachers and authorities; and the secondary data taken from the result of relevant literature studies. The collected data were analyzed using an approach adapted from the ESP concept introduced by Dudley-Evans. The study shows that Arabic for special purposes both in Indonesia and in Malaysia was practiced by several educational and non-educational institutions. The teaching of Arabic language for academic purposes at STFI Sadra Jakarta uses a strategy for comprehending the text and other literatures on Quran and its interpretation. Arabic for vocational purposes at PT. Mutiara Bahari Alamria, Bekasi uses an oral communication strategy that focuses on everyday language and vocabulary. Arabic for religious purposes at LBIQ Jakarta is directed mainly at the acquisition of Quranic Arabic. While, the teaching of Arabic at IIUM (International Islamic University Malaysia) is directed at the mastery of academic and religious purposes to meet the special needs, such as Business, Tourism, Medical, Hajj and Umrah; and for ordinary people to understand the Quran and worship. The teaching of Arabic for academic purposes in Malaysia is also done by Akademi Pengajian Islam, Universiti Malaya (APIUM) with an emphasis on understanding Sharia and Fiqh in Arabic. Arabic for vocational purposes at UPNM-Kuala Lumpur is carried out with strategies covering Arabic language competition activities such as Arabic debate, Arabic speech, and apprenticeship activities in native Arabic speakers' families. Artikel ini bertujuan untuk mengungkap paradigma bahasa Arab untuk tujuan khusus di Indonesia dan Malaysia melalui lembaga-lembaga formal dan informal. Penelitian ini merupakan penelitian kualitatif lapangan yang data primernya diperoleh dari dokumen kurikulum dan wawancara dengan guru dan pihak yang berwewenang; data sekunder diperoleh dari hasil kajian literatur yang relevan. Data penelitian dianalisis dengan menggunakan pendekatan yang diadaptasi konsep ESP yang diperkenalkan oleh Dudley-Evans. Hasil penelitian memperlihatkan Bahasa Arab untuk tujuan khusus baik di Indonesia maupun di Malaysia dipraktikkan oleh beberapa lembaga pendidikan dan nonkependidikan. Bahasa arab untuk tujuan akdemik di STFI Sadra Jakarta menggunakan strategi pemahaman teks dan literatur Alquran dan tafsir. Bahasa Arab untuk tujuan pekerjaan di PT. Mutiara Bahari Alamria, Bekasi menggunakan strategi komunikasi secara lisan yang berfokus pada kosakata. Bahasa Arab untuk tujuan agama di LBIQ Jakarta diarahkan pada bahasa Arab Qurani. Bahasa Arab di IIUM (International Islamic University Malaysia) diarahkan pada tujuan akademik dan agama untuk memenuhi kebutuhan bidang khusus seperti Bisnis, Pariwisata, Medis, haji dan umrah; dan untuk memahami Alquran dan ibadah bagi orang awam. Bahasa Arab untuk tujuan akademik di Malaysia juga dipraktikkan oleh Akademi Pengajian Islam, Universiti Malaya (APIUM) dengan penekanan pada pemahaman Syariah dan Fiqih berbahasa Arab. Bahasa Arab untuk tujuan pekerjaan di UPNM-Kuala Lumpur dilakukan dengan strategi kegiatan kompetisi bahasa Arab seperti debat bahasa Arab, pidato bahasa Arab, dan kegiatan magang di keluarga penutur asli bahasa Arab. تهدف هذه المقالة إلى الكشف عن النموذج العربي لأغراض خاصة في إندونيسيا وماليزيا من خلال مؤسسات رسمية وغير رسمية. هذا البحث هو بحث نوعي ومجال عن طريق الإشارة إلى تصنيف Dudley-Evans للغة الإنجليزية لأغراض خاصة (ESP) . البيانات الأولية من وثائق المناهج والمقابلات مع المعلمين. أما البيانات الثانوية فهي من نتائج مراجعة الأدبيات موثوقة وذات صلة. تمارس اللغة العربية للأغراض الخاصة في إندونيسيا بشكل خاص من قبل STFI Sadra Jakarta، PT. Mutiara Bahari Alamria ، و (معهد اللغة والعلوم من القرآن الكريم) LBIQ جاكرتا. بينما تمارس في ماليزيا من قبل IIUM (الجامعة الإسلامية الدولية في ماليزيا) ، وأكاديمية الدراسات الإسلامية، وجامعة مالايا (APIUM) ، UPNM- كوالالمبور. تستخدم اللغة العربية للأغراض الأكاديمية في STFI Sadra Jakarta استراتيجية لفهم النص وأدب القرآن وتفسيره. اللغة العربية لأغراض العمل في حزب العمال. Mutiara Bahari Alamria Jatirangon Jatisampurna ، Bekasi يستخدم استراتيجية التواصل اللفظي في سياق المساعدين المنزلية مع التركيز على المفردات (المفردات). اللغة العربية لأغراض دينية في LBIQ جاكرتا موجهة إلى القرآن العربية. يتم توجيه اللغة العربية في الجامعة الإسلامية الدولية في ماليزيا إلى الأهداف الأكاديمية والدينية لتلبية الاحتياجات التي تركز على مجالات معينة مثل الأعمال والسياحة والطب والحج والعمرة وفهم القرآن والعبادة للناس العاديين. تمارس الأهداف الأكاديمية الخاصة في ماليزيا من قبل أكاديمية الدراسات الإسلامية ، Universiti Malaya (APIUM) مع استراتيجيات لاستخدام مقالات حول الشريعة والفقه العربي. يتم تنفيذ اللغة العربية لأغراض العمل في UPNM-Kuala Lumpur من خلال استراتيجيات نشاط المنافسة العربية مثل المناقشات العربية والخطب العربية وأنشطة التدريب المهني في عائلات الناطقين باللغة العربية.